Penilaian Potensi Wisata Alam di Taman Nasional Kerinci Seblat Wilayah IV Sangir - Akbar, Bayu; Novio, Rery (Lembaga Yasin AlSys, 2024)
National park areas in Indonesia have biodiversity which can be a special attraction for tourists. The aim of this research is to determine the attractiveness, access to tourist attraction locations, and classification of the feasibility of potential natural tourist attractions in South Solok Regency. The research method uses the Analysis Guidelines for Assessment of Operational Areas-Objects and Natural Tourism Attractions. There are six natural tourism potentials, namely, Ulu Tulisi Waterfall, Andalas Waterfall, Pincuran Tujuh, Bukit Bontak Lake, Mount Kerinci Climbing Route via South Solok, and Sungai Dalam Lake Bukit Bontak Waterfall and the Mount Kerinci Climbing Route via South Solok have high scores. highest in the attraction aspect and accessibility aspect. Based on the assessment of both aspects, Bukit Bontak Lake and the Mount Kerinci Climbing Route via South Solok are the main priorities because they received the very worthy category. The results of this analysis can determine the direction of development of natural tourist attractions in the Sangir Region IV National Park Management Section.